Living Standards in the Past : New Perspectives on Well-Being in Asia and Europe. - Allen, Robert C. (OUP Oxford, 2005)
Why did Europe experience industrialisation and modern economic growth before China, India or Japan? This is one of the most fundamental questions in Economic History and one that has provoked intense debate. The main concern of this book is to determine when the gap in living standards between the East and the West emerged. The established view, dating back to Adam Smith, is that the gap emerged long before the Industrial Revolution, perhaps thousands of years ago. While this view has been called into question - and many of the explanations for it greatly undermined - the issue demands much more empirical research than has yet been undertaken. How did the standard of living in Europe and Asia compare in the seventeenth and eighteenth centuries? The present book proposes an answer by considering evidence of three sorts. The first is economic, focusing on income, food production, wages, and prices. The second is demographic, comparing heights, life expectancy and other demographic indicators. The third combines the economic and demographic by investigating the demographic vulnerability to short-term economic stress.